Adsorption of PCE in alkali‐activated materials analysed by fluorescence microscopy. (3rd November 2021) - Wetzel, Alexander; Link, Janna; Middendorf, Bernhard
Abstract: The realisation of high‐performance concrete mixtures requires the use of superplasticizers to achieve a low water/binder ratio and thus high strengths. Polycarboxylate ethers (PCE) are mostly used as superplasticizers. The effectiveness of these superplasticizers depends on their chemical structure, the binders' alkaline environment and the ions present in the pore solution of the binder. In high alkaline systems like some alkali‐activated materials no effective superplasticizer have been found yet. To unravel the compatibility of certain PCE to such a highly alkaline system a fluorescence microscopy approach was used. In first experiments, the adsorption of APEG (allyl ether) and MPEG (methacrylate) PCE on ground granulated blast furnace slag and fly ash was investigated varying the concentration of the activators. At a certain concentration, a complexation of the PCE can be recognised in fluorescence microscope. APEG shows a better stability compared to MPEG; this correlates with rheological investigations.